Role of xanthan gum on physicochemical and rheological properties of rice bran oil emulsion - Saharudin, Siti Hajar; Ahmad, Zalinah; Basri, Mahiran (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Xanthan gum is a high molecular weight substance with potential in improving emulsions properties. The formulation composition was selected on Tween 80 ternary phase diagram and was modified by the addition of xanthan gum at different concentrations (0.0% – 1.0%). The main objective of this study was to determine the effect of xanthan gum on physicochemical and rheological properties of rice bran oil emulsion. Xanthan gum concentrations have affected the formulations droplet size. Yet, they did not show any effect on pH of the formulations. However, an increase in xanthan gum concentration had increased the zeta potential value, stability, and viscosity of the formulations. Xanthan gum also enhanced the flow behaviour of the formulations.